2020
DOI: 10.3390/cancers12092460
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Role of CD271 in Melanoma

Abstract: The evolution of melanoma, the most aggressive type of skin cancer, is triggered by driver mutations that are acquired in the coding regions of particularly BRAF (rat fibrosarcoma serine/threonine kinase, isoform B) or NRAS (neuroblastoma-type ras sarcoma virus) in melanocytes. Although driver mutations strongly determine tumor progression, additional factors are likely required and prerequisite for melanoma formation. Melanocytes are formed during vertebrate development in a well-controlled differentiation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 119 publications
(186 reference statements)
1
21
0
1
Order By: Relevance
“…The expression of the latter nerve growth factor receptor (CD271) and putative marker of melanoma initiating cells sufficiently mediated resistance to vemurafenib in vitro and was associated with lymph node metastasis in melanoma patients [2][3][4][5][6][7]. Melanoma cells expressing NGFR exhibit increased migratory, invasive and survival capacities and the knockdown of this TNF-receptor family member revealed a network of NGFR/CD271-associated genes that facilitate and maintain different phenotypes [8][9][10][11][12]. Although NGFR-mediated signaling mechanisms are still not well understood in melanoma and cancer, several lines of evidence suggest that NGFR serves as a regulator of basic tumor cell properties such as plasticity, hence, non-genetic and reversible switching of cellular phenotypes [13][14][15][16] likely triggered by environmental cues causing stress.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the latter nerve growth factor receptor (CD271) and putative marker of melanoma initiating cells sufficiently mediated resistance to vemurafenib in vitro and was associated with lymph node metastasis in melanoma patients [2][3][4][5][6][7]. Melanoma cells expressing NGFR exhibit increased migratory, invasive and survival capacities and the knockdown of this TNF-receptor family member revealed a network of NGFR/CD271-associated genes that facilitate and maintain different phenotypes [8][9][10][11][12]. Although NGFR-mediated signaling mechanisms are still not well understood in melanoma and cancer, several lines of evidence suggest that NGFR serves as a regulator of basic tumor cell properties such as plasticity, hence, non-genetic and reversible switching of cellular phenotypes [13][14][15][16] likely triggered by environmental cues causing stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cellular plasticity probably controls the interconversion of stem-like and non-stem-like tumor cells. The expression of NGFR/CD271 was associated with melanoma cell stemness 3,11,12,23 , however we observed that the CD271 + population contains a label-retaining subset and hence comprises a proliferating non-stem like and a slow-cycling fraction that likely presents the actual subset of melanoma initiating cells 11,12 . These previous findings suggest that CD271 labels a heterogeneous pool of melanoma cells which likely feature unique and common properties.…”
Section: Resultsmentioning
confidence: 71%
“…The expression of the latter nerve growth factor receptor (CD271) and putative marker of melanoma initiating cells sufficiently mediated resistance to vemurafenib in vitro and was associated with lymph node metastasis in melanoma patients [2][3][4][5][6][7] . Melanoma cells expressing NGFR exhibit increased migratory, invasive and survival capacities and the knockdown of this TNF-receptor family member revealed a network of NGFR/CD271-associated genes that facilitate and maintain the different phenotypes [8][9][10][11][12] . Although NGFR-mediated signaling mechanisms are still not well understood in melanoma and cancer, several lines of evidence suggest that NGFR serves as a regulator of basic tumor cell properties such as plasticity, hence non-genetic and reversible switching of cellular phenotypes [13][14][15][16] , likely triggered by environmental cues causing stress.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other studies have suggested that CD271 may contribute to the aggressive nature of melanoma cells and associated chemoresistance [154,155]. Another functional driver of melanoma aggressiveness and drug resistance is ATP-binding cassette sub-family member 5 (ABCB5), which promotes drug efflux in cancer cells [156].…”
Section: Oral Melanomamentioning
confidence: 99%
“…High variability was observed in the expression of CD271 as a CSC marker and some controversy still exists with regard to its function in melanoma stem cells. Nevertheless, other studies have suggested that CD271 may contribute to the aggressive nature of melanoma cells and associated chemoresistance [ 154 , 155 ]. Another functional driver of melanoma aggressiveness and drug resistance is ATP-binding cassette sub-family member 5 (ABCB5), which promotes drug efflux in cancer cells [ 156 ].…”
Section: Characterization Of Oral Non-scc Cancer Stem Cellsmentioning
confidence: 99%